การพัฒนาการดำเนินงานตามระบบดูแลช่วยเหลือนักเรียน โรงเรียนพร้าววิทยาคม อำเภอพร้าว จังหวัดเชียงใหม่ - การุณ เชิดชู (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The objective of this study is to study the problem and the improvement guideline including to the development guideline for procedure development according to the system of taking care and helping students in Phrao Wittayakom school, Phrao district, Chiang Mai province. There are 3 procedures of the study; the first procedure was to study the problem and improvement guideline of the procedure development according to the system of taking care and helping students in Phrao Wittayakom school. The sample for this study were educational institute administrators, teachers, educational staff, and parents of Phrao Wittayakom school, Chiang Mai province. The tool for this study were questionnaires. The data was analyzed by means and standard deviation values. The second step was to draft the development guideline of procedure development according to the system of taking care and helping students in Phrao Wittayakom school, Chiang Mai province. The sample for this step were specific which were the expert, people who responsible to educational procedure and the system of taking care and helping students, 9 of them. The tool for this step were focus group discussion, data analyze, analyze interpretation, synthesis and the summary of the focus group discussion. The third step was to examine the draft of development guideline for procedure development according to the system of taking care and helping students in Phrao Wittayakom school. The objective of this step was to examine the draft from the second step. The sample for this step were university teachers who have experience in taking care and helping students, administrators, teacher who responsible to the taking care and helping students system from the school and the experts of taking care and helping students, 5 of them. the tool for this step were the check form of appropriate level of possibility, appropriate and productivity. The data was analyzed by using the value of means and standard deviation. It was found that the problem of procedure of taking care and helping students system overall was in moderate level and when considering one by one it was found that 1) students promotion, the overall was in moderate level and the point that have the highest value was the school provided less the opportunity to the student to participate in determination of rules and regulations for any activities. The improvement guideline was to adjust the plan to be more appropriate, usable and everyone must follow the plan. The suggestion was to have the student know themselves, thing positively and be optimistic. 2) Prevention and solving the problem overall was in moderate level. The point that had the highest value was the school provided less activity of friend supporting friend. the solution for this problem was to have more cooperation between the taking care and helping students system, homeroom teacher and parents. they should have checked all documents and solving the problem more seriously. the suggestion was to have the students be more optimistic, helping one another and sacrifice to the society. For the development guideline for procedure development according to the system of taking care and helping students, it was found that 1) student promotion must improve procedure plan to be more appropriate and usable and 2) the prevention and solving the problem must provide more activities which the students are interested, have the student have more participation in helping one another, encourage them and hold some seminar to provide more knowledge of taking care and helping student in each level. The possibility examination, appropriate and productivity of the development guideline for procedure development according to the system of taking care and helping students in Phrao Wittayakom school, Phrao district, Chiang Mai province were in the highest level, over the determined standards.